-6+4(3x-13)=82

Simple and best practice solution for -6+4(3x-13)=82 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6+4(3x-13)=82 equation:


Simplifying
-6 + 4(3x + -13) = 82

Reorder the terms:
-6 + 4(-13 + 3x) = 82
-6 + (-13 * 4 + 3x * 4) = 82
-6 + (-52 + 12x) = 82

Combine like terms: -6 + -52 = -58
-58 + 12x = 82

Solving
-58 + 12x = 82

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '58' to each side of the equation.
-58 + 58 + 12x = 82 + 58

Combine like terms: -58 + 58 = 0
0 + 12x = 82 + 58
12x = 82 + 58

Combine like terms: 82 + 58 = 140
12x = 140

Divide each side by '12'.
x = 11.66666667

Simplifying
x = 11.66666667

See similar equations:

| 2*y-3*y=5 | | 8x+1=1.528 | | -2m-8m=10 | | 24x=24x-27 | | (x+7)2+(y-1)2=32 | | x=52.5(2/5) | | u^2=3u | | k(x)=2x^2+33x-54 | | x=40(2/5) | | 11=11-10b+2b | | s-3=-5 | | 210.00+0.15x=322.50 | | 4-2=10 | | 3x=2+-1y | | 10x+9=27+7x | | f(-1)=5x+5 | | -(a+3)=-2(2x+3)-7 | | 2(t+2)=14 | | 81xsquared+8=0 | | f=-1 | | 41(x-6)+4=6x-8 | | 9x+7(3x-4)=7-5x | | 4x-2(x-3)=-5+4x+1 | | 9v-9=3(v-5) | | 2x^2+x^2=25*25 | | 4-2(x-3)=5+4x+1 | | 4x-15=x+51 | | 0.5x+9= | | 208=-13 | | 12x^3+28x^2+13x-45=0 | | 3x+10=7x-5 | | 25x^4-50x^3+25x^2=0 |

Equations solver categories